Cahokia$s Boom and Bust in the Context of Climate Change. Issue 3 (20th July 2009) - Benson, Larry V.; Pauketat, Timothy R.; Cook, Edward R.
Abstract : During the early Mississippian Lohmann phase (A.D. 1050-1100), the American Bottom experienced a political and economic transformation. This transformation included the abrupt planned construction of central Cahokia, a large-scale influx of people to "downtown Cahokia, " the abandonment of pre-Mississippian village settlements, the reorganization of farming in the Mississippi River floodplain, and the founding of the Richland farming complex in the Illinois uplands. New tree-ring-based records of climate change indicate that this rapid development occurred during one of the wettest 50-year periods during the last millennium. During the next 150 years, a series of persistent droughts occurred in the Cahokian area which may be related to the eventual abandonment of the American Bottom. By A.D. 1150, in the latter part of a severe 15-year drought, the Richland farming complex was mostly abandoned, eliminating an integral part of Cahokia$s agricultural base. At about the same time, a 20, 000-log palisade was erected around Monks Mound and the Grand Plaza, indicating increased social unrest. During this time, people began exiting Cahokia and, by the end of the Stirling phase (A.D. 1200), Cahokia$s population had decreased by about 50 percent and by A.D. 1350, Cahokia and much of the central Mississippi valley had been abandoned.